The Influence ofElectronic Word Of Mouth (EWOM) on Purchase Intention Mediated byBrand Image (A Study on Starbucks’ College Students Consumer at Malang) - WIDADSYAH, MUHAMMAD AZHAR (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This research examines the influence of electronic word of mouth on purchase intention mediated by brand image on Starbucks’ college student consumers in Malang. This explanatory research explains the causal relationship between its variables through hypothesis testing. The sample of this research were selected using non-probability sampling technique with purposive sampling methods. This research examines responses from 150 college students in Malang who have social media account and are 17 years of age at the minimum. The hypotheses were examined using Path Coefficient and Sobel Test, and the data were analyzed using Partial Least Square in Smart PLS 3.0 software. The result shows that electronic word of mouth has a positive and significant effect on brand image at the value of 0.6393. It also has a positive and significant effect on purchase intention at the value of 0.3229. Furthermore, brand image has a positive and significant effect on purchase intention at the value of 0.4962. Finally, electronic word of mouth has a positive and significant effect on purchase intention mediated by brand image at the value of 0.3172. Keywords: electronic word of mouth, brand image, purchase intention, Starbucks